Best practices for television journalists a handbook for reporters, producers, videographers, news directors and other broadcast professionals on how to be fair to the public - Westin, Av 1929- (Freedom Forum, 2000)
A handbook of best practices for television and broadcast journalists, encouraging practices that the public will see as being fair, thereby helping assure that television news gathering remains free.